2006
DOI: 10.2174/138920006776359293
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of the Experimental Design of Studies of Mechanism Based Enzyme Inhibition, with Implications for In Vitro-In Vivo Extrapolation

Abstract: The published literature on mechanism based inhibition (MBI) of CYPs was evaluated with respect to experimental design, methodology and data analysis. Significant variation was apparent in the dilution factor, ratio of preincubation to incubation times and probe substrate concentrations used, and there were some anomalies in the estimation of associated kinetic parameters (k(inact), K(I), r). The impact of the application of inaccurate values of k(inact) and K(I) when extrapolating to the extent of inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 17 publications
4
115
0
1
Order By: Relevance
“…In the present work, values for k deg were used that were derived from modeling of the time course of reversal of DDIs caused by induction or inactivation of P450 enzymes in human study subjects. The values obtained were substantially lower than the rat value, were within values reported in Ghanbari et al (2006), and when used generally led to over-prediction of the magnitude of DDIs (i.e., lower k deg leads to greater DDI). Actual measurements of P450 enzyme k deg values in humans in vivo are not obtainable with technology presently available, leaving this parameter as one important source of potential error in DDI predictions for inactivators.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In the present work, values for k deg were used that were derived from modeling of the time course of reversal of DDIs caused by induction or inactivation of P450 enzymes in human study subjects. The values obtained were substantially lower than the rat value, were within values reported in Ghanbari et al (2006), and when used generally led to over-prediction of the magnitude of DDIs (i.e., lower k deg leads to greater DDI). Actual measurements of P450 enzyme k deg values in humans in vivo are not obtainable with technology presently available, leaving this parameter as one important source of potential error in DDI predictions for inactivators.…”
Section: Discussionsupporting
confidence: 54%
“…Also, there are aspects of in vitro experimental design that can yield variability and inaccuracy. These have been discussed in a recent article by Ghanbari et al (2006). The four parameters that are most important to making accurate predictions of DDIs caused by inactivators are 1) the in vivo rate of enzyme degradation, k deg , 2) the relevant in vivo concentration of the inactivator, [I], available to the target enzyme, 3) the in vitro inactivation kinetic parameters (K I and k inact ), and 4) the fraction of the clearance of the affected drug that is mediated by the inactivated enzyme.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous study, k e estimates ranging from 0.0005 to 0.00026 min Ϫ1 yielded the most accurate in vivo predictions of CYP1A2 inhibition by the mechanism-based inhibitor zileuton . In our simulations, a CYP1A2 half-life of 38.6 h (i.e., k e ϭ 0.0003 min Ϫ1 ) was assumed, based on a previous estimate of the in vivo CYP1A2 half-life (Faber and Fuhr, 2004;Ghanbari et al, 2006). This value is similar to the in vitro half-life estimate of 36 h determined for CYP1A2 in liver slices (Renwick et al, 2000).…”
Section: Karjalainen Et Almentioning
confidence: 91%
“…Ghanbari et al have shown that many published studies of TDI which followed this method were limited by insufficient enzyme dilution and over-long incubation times (36). However, with increased LC-MS/MS method sensitivity it is possible to minimise the Fig.…”
Section: Tdi Methods: Preincubation-dilution-incubation Methodsmentioning
confidence: 99%